AKIBAT HUKUM AKUISISI PERUSAHAAN TERHADAP LISENSI MEREK - sudjana, sudjana (Veritas et Justitia, 2022)
This study aims to obtain information regarding the legal consequences in the event of an Acquisition of ownership of rights to a Mark and to determine the legal protection of the Brand Licensee against cancellation by the Acquirer. The type of legal research used is normative using qualitative analysis techniques. The results of the study show that the company's acquisition does not have a legal effect on the transfer of ownership of the rights to the Mark because the meaning of the Acquisition contained in the Company Law is the Acquisition of Shares, so that the Acquired party remains the owner of the rights to the Mark. Whereas in Asset Acquisition if the Acquired company transfers the Assets including ownership of the rights to the Mark to the Acquirer, there will be a change in the parties in the Mark Licensing agreement, resulting in legal consequences for the fulfillment of achievements or royalty payments. In the event of the cancellation of the Mark License Agreement by the Acquirer, the Mark Licensee shall receive protection under the Law of the Agreement by filing a breach of contract according to Article 1243 of the Civil Code because Law of Mark and geographical indication only protects the Licensee against the deletion of the registered mark but the Licensee must agree in writing unless agreed otherwise.